Continuing debt crisis of the developing countries ([s.n.] [S.l.], 1994)
Looks at the new developments in the international debt crisis which emerged in the 1980s. Discusses a possible approach to debt reduction and reorganisation for the 55-60 developing countries facing a serious debt crisis at present. Suggests that the debt overhang of other developing countries be carefully monitored, since an adverse economic environment in these countries would aggravate the extent of the present problem.
DC